Crystal structure and optical properties of quaternary systems of Bi-Sb-Te-Se - Abou El Soud, A. M. (Array, 2008)
Summary: The quaternary systems of Bi-Sb-Te-Se were synthesized by direct fusion technique. Thin films of these compounds were prepared by thermal evaporation under vacuum of 10-4 Pa. The structural properties of these compounds in powder and thin film forms were investigated by X-ray diffraction. The optical constants (absorption coefficient and band gap) of the thin films were determined by measurements of IR absorbance in the region 2.5 - 10 mm. Analysis of the optical absorption spectra revealed the existence of two direct energy gaps